Detection of Helicobacter spp in the gastric mucosa of clinically healthy domestic felines by the rapid urease test and histopathology - Thomson, Pamela (2020)
The aim of this study was to detect Helicobacter spp through the rapid urease test and histopathology in clinically healthy domestic felines (Felis silvestris catus) and to establish the degree of concordance between both methods. Fifteen cats without clinical signs of gastrointestinal disease, between 2 and 7 years old, without distinction of breed and sex, without dietary changes and without having undergone antibiotic or proton pump inhibitor therapy in the last 90 days were included. Endoscopy was performed to macroscopically evaluate the gastric mucosa and obtain biopsies of the gastric fundus and body. It was determined, with both tests, that 86.6% of the samples were positive for the presence of Helicobacter spp, finding 100% concordance between the two tests. In 40% (6/15) of the felines macroscopic lesions were observed in the gastric mucosa, but no association was found between the lesions with the presence of Helicobacter spp. It is concluded that 86.6% of the felines presented colonization by Helicobacter spp, and that the rapid urease test constitutes a reliable method for the diagnosis of infection by Helicobacter spp.